Seasonal performance of three elite Hevea(Rubber) clones in less favourably suited edaphic and climatic conditions of Orissa - Gupta C; Edathil T T; Rao K N (Proceedings of the 15th Plantation Crops Symposium, PLACROSYM XV, 10-13 December 2002, Mysore .pp.64-71.)
Effect of seasonal changes on the growth and yield performance of three elite Hevea cloens (RRII 105, RRIM 600 and GT 1) was studied in the warm dry sub humid region of Orissa, which is a non-traditional rubber growing area where the crop experiences severe drought in summer months. The soil characters are only marginally suited, when compared to that of traditional belt of rubber growing areas. Prolonged soil moisture stress, high wind speed and high summer temperature are the major environmental constraints affecting the growth of rubber in this region. The relative growth rate declined drastically in all the elite clones screened with increase in age of the plants. The mean annual girth increment was 4.4-cm. Highest girth increment was recorded in RRIM 600 closely followed by GT 1 and RRII 105. Maximum growth was recorded during post monsoon (September-November, 53 per cent) followed by monsoon season (June-August, 33 per cent), while lowest growth was observed during summer (March-May, 6 per cent). In spite of life saving irrigation in summer, the seasonal growth was low in the dry sub humid region region of Orissa. In general, RRIM 600 maintained relatively higher seasonal performance followed by GT 1 in growth and RRII 105 in both growth and yield performance. RRIM 600 recorded highest dry rubber yield (24.8 g/tree/tap) over the first two years of tapping followed by RRII 105 (22.0g/tree/tap) and GT 1 (18.2 g/tree/tap). The projected commercial mean yield of RRIM 600 is 992 kg/ha/400 trees, followed by RRII 105 (880 kg) and GT 1 (728kg). An attempt was also made to study the influence of seasonal hydro-meteorological parameters like temperature, relative humidity, rainfall evaporation and sunshine hours on the growth and yield of rubber in this region. Correlation and regression of seasonal RGR with climatic parameters are discussed in this paper.
Keywords: Edaphic condition; Hevea; Orissa; Seasonal performance